Efektivitas Metode Shaping untuk Mengurangi Perilaku Maladaptif pada Anak dengan Attention Deficit Hyperactivity Disorder (ADHD) (Single Subject Research di SD Negeri 12 Pisang) - Zuri Aqti Aqyun; Marlina; Mega Iswari; Yosa Yulia Nasir (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effectiveness of the shaping method in reducing maladaptive behavior in children with ADHD at Pisang 12 Public Elementary School. The study used an experimental approach with the Single Subject Research (SSR) method with a reversal design (A1–B–A2), which consisted of an initial baseline phase (A1), an intervention phase (B), and a second baseline phase (A2). The subject of the study was a child with ADHD who exhibited maladaptive behaviors such as disturbing friends, shouting, throwing objects, and difficulty sitting still in class. Data were collected through direct observation using a frequency recording sheet of target behaviors during the learning process. Data analysis was carried out visually within and between conditions, including directional trends, data stability, level changes, and percentage overlap. The results showed that in the initial baseline condition (A1), the frequency of maladaptive behavior was at 10 events with a horizontal trend. After being given intervention using the shaping method in the intervention phase (B), the frequency of maladaptive behavior decreased to 4–6 events with a downward trend. In the second baseline condition (A2), the frequency of maladaptive behavior remained at a lower level, namely 3–4 events. The overlap between conditions A1 and B was 0%, while between conditions B and A2 it was 33.3%. These results indicate that the shaping method is effective in reducing maladaptive behavior in children with ADHD.